Teaching English. Teaching thinking (Journal of Parents and Teachers, 2012)
The primary objective of learning a foreign language is to develop communicative competence, and competence entails the ability to express thoughts. In this article, the author uses Bloom’s taxonomy to create activities that help learners to express thoughts on two levels, lower and higher order learning skills: LOTS and HOTS through specific activities. Activities based on graphic organizers enable learners to express thoughts briefly and visually. They provide scaffolding for activating knowledge, making comparisons, examining cause and effect and summarizing. Asking and answering questions are a major part of all language classes, so the author offers suggestions for developing thinking skills through questioning. Formulating questions on stories reinforces language and cognitive skills while developing literacy when carried out within a framework of collaborative learning. All the activities can be adapted to the learner’s language level and different ages, so teachers are encouraged to experiment with them, and make changes to suit their learners.
Keywords: thinking skills; Bloom; collaborative learning; graphic organizers; stories; experiencies